S71 Are ethnic differences in lung function explained by differences in respiratory muscle strength in children?. (15th November 2017) - Gharbawi, NTS; Duncan, G; Gaillard, EA; Viskaduraki, M; Beardsmore, CS
Abstract : Background: South Asian (SA) children have a reduction in forced vital capacity (FVC) of 9%–13% compare to white children. Ethnic differences in Maximal Inspiratory Pressure (MIP) and Maximal Expiratory Pressure (MEP) could potentially explain this. One study in adults measured MIP (but not MEP) in four ethnic groups (not including South Asians) but failed to find any differences (Sachs, Enright et al . 2009). Aim: To investigate differences in spirometry and respiratory muscle strength between white and south Asian children. Methods: Children were recruited from primary schools. We measured height, weight, and spirometry. FEV1 and FVC were expressed as Z-scores, based on predicted values for white children (Quanjer et al . 2012). For respiratory muscle strength measurements, the child breathed through a pneumotachograph attached to a shutter. To measure MIP, after several quiet breaths, the child exhaled maximally and the shutter was activated. The child made an inspiratory effort and peak pressure was recorded. The test was repeated several times. Measurements of MEP were similar, except that the child inhaled maximally and then made a forceful expiratory effort. Results: We studied 263 healthy children aged 5–11 year. We obtained valid spirometry on 229 (64 white, 165 SA); valid MIP on 203 (55 white, 148 SA); and valid MEP on 231 (64 white, 167 SA). FEV1 and FVC were smaller in SA children than their white peers. There were no significant differences between unadjusted MIP and MEP in white and SA children. This finding was unchanged after adjustment for age, height and weight (Table). Conclusions: Differences in spirometry were in accordance with previous reports. We did not find any significant differences in respiratory muscle strength between the two ethnic groups. The greater FVC in white children might have been attributable to increased inspiratory muscle strength, leading to a greater volume at the start of the manoeuvre, but this was not the case. An increase in expiratory muscle strength would be less likely to increase FVC, since the end of expiration occurs when there is airway closure. Elastic recoil might be an alternative explanation for ethnic differences in lung function.